Nonliner damping of electron beam-driven Langmuir waves due to Langmuir-kinetic Alfvén-whistler coupling in the solar corona - Sirenko, O.K.; Voitenko, Yu.M.; Goossens, M.; A.C.-L., Chian (Вопросы атомной науки и техники, 2007)
We present a coherent nonlinear theory of three-wave coupling involving Langmuir, kinetic Alfvén and whistler waves. The initial stage of the energy exchange among these modes and the following nonlinear temporal dynamics are studied. The role of pump depletion, dissipation and frequency mismatch in the nonlinear wave dynamics is analyzed. Depending on the relative damping rates of the waves, the initial Langmuir waves can be nonlinearly transformed either into whistlers, or into KAWs. The theory is applied to the Langmuir waves excited by electron beams in a diluted solar corona where the local electron-cyclotron frequency is higher than the local electron plasma frequency.